Probabilistic model of fingerprint images of computer biometric authentication - Shlokin, V.M.; Rasomakhin, S.G. (Radiotekhnika, 2018)
Methods of computer biometric authentication are analyzed. Peculiarities of the identification process of fingerprints characteristic features are investigated. A probabilistic model of fingerprint images is proposed. The nature and sources of errors in the processing of imaging portraits under the conditions of distorting influences are grounded. The descriptions and characteristics of error distributions are obtained.